PENDEKATAN LAYANAN BIMBINGAN DAN KONSELING ANAK BERKEBUTUHAN KHUSUS - Supiartina Supiartina; Rendra Khaldun (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2018)
Special Needs Children (ABK) are individuals who have characteristics that are different from other individuals in the normal view of society in general. More specifcally, children with special needs show lower intellectual or emotional characteristics or higher than normal anal peers or are outside the normal standards that apply in society. So that it has diffculty in achieving success both in terms of social personal, and educational activities. especially what they have makes children with special needs need special education and services to optimize their inner potential. The impact of negative developments raises the risk of increasing the likelihood of the emergence of diffculties in adjustment to disabled children so that supporting factors are needed to adjust. Environment as an important factor to adjust. The attitude of parents, family, peers, school friends, and the general public as supporters in adjusting to their environment.